Energy Consumption and Economic Growth in South Africa: Evidence from Provincial Panel Data - Ramabu, Naledi; Sithole, Kabelo (Energy Insights, 2026)
Objective: This study investigates the relationship between electricity consumption and regional economic growth across South African provinces, addressing limitations of prior research that primarily utilized national-level time-series data. The research aims to provide empirical evidence on how energy use and key macroeconomic factors influence provincial economic performance. Methods: A quantitative panel data approach was employed, utilizing annual secondary data from South African provinces. Economic growth was modeled as a function of electricity consumption, population, domestic investment, and government expenditure. Model selection was conducted using Chow and Hausman tests, resulting in the application of a fixed-effect regression model with robust standard errors to mitigate the effects of heteroskedasticity. Results: The findings reveal that electricity consumption has a positive and statistically significant impact on regional economic growth. Domestic investment and government expenditure also significantly promote economic expansion, with public spending emerging as the most dominant driver. Conversely, population growth does not exhibit a significant effect. The model demonstrates strong explanatory power, accounting for approximately 89.3% of the variation in economic growth. Novelty: This study contributes novel provincial-level empirical evidence on the energy-growth nexus in South Africa, utilizing a robust panel econometric framework. By integrating energy consumption with fiscal and investment factors, it offers a more comprehensive understanding of regional growth dynamics and provides policy-relevant insights for sustainable energy and economic development.